Peripheral blood late mixed chimerism in leucocyte subpopulations following allogeneic stem cell transplantation for childhood malignancies: does it matter?. (21st March 2016) - Pichler, Herbert; Fritsch, Gerhard; König, Margit; Daxberger, Helga; Glogova, Evgenia; Pötschger, Ulrike; Breuer, Sabine; Lawitschka, Anita; Güclü, Ece D.; Karlhuber, Susanne; Holter, Wolfgang; Haas, Oskar A.; et al.
Summary: The impact of persistent mixed chimerism (MC) after haematopoietic stem cell transplantation (HSCT) remains unclarified. We investigated the incidence of MC in peripheral blood beyond day +50 after HSCT and its impact on rejection, chronic graft‐versus‐host disease (c‐GvHD) and relapse in 161 children receiving allogeneic HSCT for haematological malignancies. The 1‐year incidence of late MC was 26%. Spontaneous conversion to complete donor chimerism (CC) occurred in 43% of patients as compared to 62% after donor lymphocyte infusions. No graft rejection occurred. The 1‐year incidence of c‐GvHD was 20 ± 7% for MC, and 18 ± 4% for CC patients ( P  = 0·734). The 3‐year cumulative incidence of relapse (CIR) according to chimerism status at days +50 and +100 was 22 ± 4% for CC patients vs. 22 ± 8% for MC patients (day +50; P  = 0·935) and 21 ± 4% vs. 20 ± 7% (day +100; P  = 0·907). Three‐year CIRs in patients with persistent MC and patients with CC/limited MC were comparable (8 ± 7% vs. 19 ± 4%; P  = 0·960). HSCT for acute leukaemia or myelodysplastic syndrome as secondary malignancies (hazard ratio (HR) 4·7; P  = 0·008), for AML (HR 3·0; P  = 0·02) and from mismatched donors (HR 3·1; P  = 0·03) were independent factors associated with relapse. Our data suggest that late MC neither protects from c‐GvHD nor does it reliably predict impending disease relapse.